1991
DOI: 10.1901/jeab.1991.55-287
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Instructions in the Transfer of Ordinal Functions Through Equivalence Classes

Abstract: In two experiments, adult subjects completed match-to-sample training and testing to establish four equivalence classes of four figures each. Then the subjects were taught one three-position sequence consisting of one stimulus from Class 1, one from Class 2, and one from Class 3. Inclusion of Class 4 stimuli in sequences was never reinforced, but two different stimuli from Class 4 appeared as distractors on each sequence trial. Tests assessed whether subjects would produce novel three-position sequences compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
8

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 21 publications
(29 reference statements)
1
42
0
8
Order By: Relevance
“…In short, transfer of function refers to the acquisition of stimulus function by virtue of membership in an equivalence class (Dougher & Markham, 1994;Hayes, 1991;Hayes & Hayes, 1989;Sidman & Tailby, 1982 There is a growing body of empirical support for the transfer of stimulus function through equivalence classes. For example, the transfer of discriminative functions has been reported by Green, Sigurdardottir, and Saunders (1991), Lazar (1977), Lazar and Kotlarchyk (1986), and Wulfert and Hayes (1988). Gatch and Osborne (1989), Kohlenberg, Hayes, and Hayes (1991), and Lynch and Green (1991) have demonstrated the transfer of contextual control, and Hayes, Kohlenberg, and Hayes (1991) have shown conditioned reinforcement and punishment functions to transfer through equivalence classes.…”
mentioning
confidence: 99%
“…In short, transfer of function refers to the acquisition of stimulus function by virtue of membership in an equivalence class (Dougher & Markham, 1994;Hayes, 1991;Hayes & Hayes, 1989;Sidman & Tailby, 1982 There is a growing body of empirical support for the transfer of stimulus function through equivalence classes. For example, the transfer of discriminative functions has been reported by Green, Sigurdardottir, and Saunders (1991), Lazar (1977), Lazar and Kotlarchyk (1986), and Wulfert and Hayes (1988). Gatch and Osborne (1989), Kohlenberg, Hayes, and Hayes (1991), and Lynch and Green (1991) have demonstrated the transfer of contextual control, and Hayes, Kohlenberg, and Hayes (1991) have shown conditioned reinforcement and punishment functions to transfer through equivalence classes.…”
mentioning
confidence: 99%
“…A produtividade do modo de investigação do responder ordinal aqui utilizado fornece uma abordagem empírica na medida em que subsidia o desenvolvimento e aplicação de tecnologias de ensino não somente da matemática, mas também de comportamentos complexos cuja ordem é a variável relevante como os gramaticais, de leitura e escrita e outros "simbóli-cos sequenciais", como sequência alfabética, espectro de cores, dias da semana e calendário com os meses do ano (por exemplo, Assis, Élleres, & Sampaio, 2006;Green, 1991;Resende, Elias, & Goyos, 2012;Ribeiro, Assis, & Enumo, 2005;Sella & Bandini, 2012;Skinner, 1957Skinner, /1957.…”
Section: Considerações Finaisunclassified
“…One line ofthought is that verbal stimuli acquire their function by their participation in equivalence classes (S. Hayes & L. Hayes, 1992;Sidman, Wynne, Maguire, & Barnes, 1989). In particular, laboratory research has demonstrated that once stimuli enter into equivalence classes, they automatically acquire the functions of the other members of the class (e.g., Gatch & Osborne, 1989;Green, Sigurdardottir, & Saunders, 1991;Lazar, 1977;Lazar & Kotlarchyk, 1986;Wulfert & S. Hayes, 1988). In this way, verbal stimuli become equivalent to the stimuli or events for which they stand and influence behavior accordingly.…”
Section: Within-session Occurrences Of Problematic Behaviormentioning
confidence: 99%